FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU IBU DALAM KUNJUNGAN NEONATAL DI WILAYAH KERJA PUSKESMAS KEDUNGMUNDU SEMARANG - Auliya Rahmawati; Besar Tirto Husodo; Zahroh Shaluhiyah (Jurnal Kesehatan Masyarakat (Undip), 2019)
More than half of infant deaths in the world occur in the first year of life, especially in the neonatal period (0-28 days baby age). Neonatal period is the most vulnerable period for infants to risk health problems. As a result of this risk, every baby must get health assistance according to standards, namely by carrying out a complete neonatal visit (KN1 – KN3). Kedungmundu Health Center is one of the ISO standard health centers in the city of Semarang whose coverage of neonatal visits has not yet reached the SPM target both in 2016 and 2017 with coverage rates below 90%. The purpose of this study was to analyze the factors related to the behavior of mothers in neonatal visits in the work area of Kedungmundu Health Center Semarang. This research is descriptive analytic with cross-sectional study design. The population were mothers who had babies aged 2-3 months,  where the sampling used a total sampling technique of 84 people. Data analysis in this study used univariate, bivariate, and multivariate analysis. The results showed that most respondents did not carry out a complete neonatal visit (66.7%). The results of the bivariate analysis using the chi-square test showed that the related variables were variables of age (p-value = 0.026), education level (p-value = 0.010), and beliefs (p-value = 0.033). The results of multivariate analysis showed the level of education was the most influential factor (OR = 5.174). There are still many mothers who are not fully equipped, it is hoped that health workers will actively conduct home visits and improve their mistaken beliefs by showing adverse effects if they do not implement KN, while puskesmas must have a strategy in delivering neonatal care materials according to their education level.